Oral fluoroquinolones and risk of aortic dissection and aortic aneurysm: a nationwide nested case-control study. (3rd October 2022) - Strange, J E; Holt, A; Christensen, D M; Gislason, G; Torp-Pedersen, C; Hansen, M L; Lamberts, M K; Schou, M; Olesen, J B; Fosboel, E L; Koeber, L; Rasmussen, P V
Abstract: Background: Oral fluoroquinolones are commonly prescribed antibiotics. Observational studies have shown an association between fluoroquinolone-use and subsequent risk of aortic aneurysm (AA) and aortic dissection (AD) due to a potential collagen degrading effect of fluoroquinolones. Purpose: To investigate if fluoroquinolone-use was associated with increased rates of AA or AD in patients without known aortic disease. Secondly, to investigate if fluoroquinolone-use was associated with increased all-cause mortality and aortic interventions in high-risk patients with known aortic disease. Methods: We used a nested case-control study design in which individuals aged 30–100 years from 2003 to 2018 were included from Danish nationwide registers. Exclusion criteria were bicuspid aortic valve, coarctation of the aorta, and connective tissue disease. A main cohort and a secondary high-risk cohort were defined. The main cohort comprised patients without history of AA/AD in which two case definitions were used: 1) A broad case definition of first-time AA/AD. 2) A severe case definition of ruptured AA/AD. The high-risk cohort comprised patients surviving index AA/AD admission in which cases were defined as all-cause mortality and aortic interventions. Cases were matched on age, sex, and year of inclusion in a 1:30 ratio with controls. For the main cohort, a potential dose-response effect was investigated using groups of cumulative defined daily doses (cDDD) of fluoroquinolones. Hazard ratios (HR) with 95% confidence intervals (CI) for fluoroquinolone-use compared with amoxicillin as an active comparator were obtained from time-dependent Cox regression models using multiple exposure windows. Results: The main cohort comprised 4.81 million individuals with 43, 280 cases. Short-term 30-day, intermediate-term 90-day, and long-term 1-year fluoroquinolone use were all not associated with AA/AD (30-day HR 1.18 [95% CI: 0.84 to 1.66]; 90-day HR 1.12 [95% CI 0.96 to 1.30]; 1-year HR 1.00 [95% CI 0.93 to 1.07]). Using a severe case definition of ruptured AA/AD yielded comparable results. For the dose-response analysis, increasing cDDD did not confer increased rates of AA/AD (1–5 cDDD: Reference group; 6–10 cDDD: HR 1.03 [95% CI: 0.87 to 1.23]; >10 cDDD: HR 1.00 [95% CI 0.83 to 1.29]) (Figure 1). The secondary high-risk cohort included 20, 195 patients surviving index admission with 9, 183 cases of all-cause mortality and 1, 768 cases of aortic interventions. The 30-day HR for all-cause mortality was 1.21 (95% CI 0.92 to 1.60) and the 60-day HR 1.06 (95% CI 0.89 to 1.26). No association with aortic interventions was found either (Figure 2). Conclusion: Fluroquinolone-use was not associated with AA/AD. Furthermore, fluoroquinolone-use was not associated with all-cause mortality or aortic interventions in potentially susceptible patients with known aortic disease. These findings do not support an increased risk of AA/AD with fluoroquinolone-use. Funding Acknowledgement: Type of funding sources: None.